Analisis Kinerja Keuangan Pemerintah Daerah Kabupaten/Kota di Jawa Tengah Periode 2012-2014 - Wilantari, Wening; , Dra. Mujiyati, M.Si (2017)
This study aims to determine the financial performance of the local government district/city in Central Java viewed from the period 2012-2014 seen from independence ratio, the ratio of efficiency and effectiveness, compatibility ratio, fiscal capacity (growth and share), the ratio of economic and dependency ratio. The population in this study are all regencies/cities in Central Java, which totaled 35 District/City. The sampling technique used in this research is purposive sampling. These results indicate that the degree of independence of the area classified as very low and the pattern of relationship instructive, the average level of effectiveness relatively effective, the average level of efficiency is categorized as less efficient, the ratio harmony explained that the results of the ratio of recurrent expenditure a higher priority than the ratio of capital expenditure, the financial capacity of the area indicated by the index growth and share classified in quadrant II and III cause conditions have not been ideal, economic ratio are economic and financial dependency ratio of the area is very high.